SUPERIOR AGRO INDUSTRY BASED ON THE PEOPLE’S ECONOMY AND ITS DEVELOPMENT STRATEGY FOR SUSTAINABILITY - Yuvanda, Sesraria; Rachmad R, Muhammad; Achmad, Erni; Zamzami, Zamzami; Abdrazakova, Ainur; Listyaningsih, Erna (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Agroindustry is a processing industry that contributes significantly to the economy of Jambi Province. Agroindustry in Jambi Province is dominated by the plantation sector. Plantations in Jambi Province produce agricultural commodities that are used as raw materials for agroindustry. The purpose of this study is to determine superior agroindustries based on community economics and then formulate appropriate strategies for the sustainable economic development of Jambi Province. The research method applied is secondary data analysis and observational analysis. Meanwhile, the analysis models used are the TOPSIS analysis model to determine leading agro-industries and the TOPSIS-SWOT analysis model to formulate development strategies. The results of the study show that the cooking oil industry was selected as the superior agro-industry. The development strategy for the selected cooking oil industry includes increasing the production capacity of palm oil plantations and CPO factories, establishing a CPO processing industry polytechnic, applying low-cholesterol technology to processed products from CPO, facilitating investment in environmentally friendly CPO factories, and increasing export quotas and controlling domestic consumption. The uniqueness of this research focuses on agro-industry development based on the criteria used in determining leading agro-industries, including business units, labour, production value, investment value, and capital turnover.